2020
DOI: 10.2478/bjmg-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of O6-methyl guanine DNA-methyl transferase promotor methylation and CpG1, CpG2, CpG3 and CpG4 methylation on treatment response and their prognostic significance in patients with glioblastoma

Abstract: This retrospective study examined the prognostic significance and treatment effect of promoter methylation of O6- methyl guanine methyl transferase (MGMT) and meth-ylation of CpG 1, CpG2, CpG3 and CpG4 in glioblastoma (GB) patients received postoperative radiotherapy (PORT), with or without adjuvant temozolomide (TMZ). One hundred patients with GB who received PORT with concomitant TMZ plus adjuvant TMZ or PORT alone, were included. The MGMT promoter methylation of CpG1, CpG2, CpG3 and CpG4 islands were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There were several limitations within the studies that we identified that may lead to bias or disparity between predicted measure of effect and true measure of effect. Many of these studies had smaller sample sizes, with some using publicly available methylation data to increase their study population [16,18,19]. Apart from studies that employed BeadChip arrays, most studies interrogated select CpG sites within the MGMT CGI, mostly due to the commercial availability of certain PSQ kits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were several limitations within the studies that we identified that may lead to bias or disparity between predicted measure of effect and true measure of effect. Many of these studies had smaller sample sizes, with some using publicly available methylation data to increase their study population [16,18,19]. Apart from studies that employed BeadChip arrays, most studies interrogated select CpG sites within the MGMT CGI, mostly due to the commercial availability of certain PSQ kits.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Yildiz et al, which has low GRADE scoring, was a Turkish study that examined the prognostic significance of MGMT methylation at 4 CpG islands [18]. However, the author does not specify the location of these "CpG islands" apart from them being located within the MGMT promoter.…”
Section: Study Descriptions and Outcomesmentioning
confidence: 99%
“…We then explored a possible mechanism for the SFPQ isoform changes seen in lung cancer. DNA methylation is an important factor in cancer development [34][35][36][37][38][39] that can lead to changes in expression [40][41][42]. We have discovered DNA methylation differences in the SFPQ promoter region which may be responsible for the SFPQ isoform expression differences between lung cancer and IPF and normal cells.…”
Section: Dna Methylation Affects Sfpq Expression In Lung Cancer and O...mentioning
confidence: 98%
“…The last study included in this systematic review, Yildiz et al was a Turkish study that examined the prognostic signi cance of MGMT methylation at 4 CpG islands 19 . However, the author does not specify the location of these "CpG islands" apart from them being located within the MGMT promoter.…”
Section: Study Descriptions and Outcomesmentioning
confidence: 99%